Physical activity and mental distress among adolescents. Results from the Tromsø Study: Fit Futures - Opdal, Ida Marie (UiT The Arctic University of Norway, 2020)
The onset of experiencing symptoms of mental distress, such as depression and anxiety, is most common during the adolescent years, and is concurrent with a measured decrease in physical activity levels. Research on the association between physical activity and mental distress among adolescents find contradictory results, and the field is in need of more longitudinal research with validated measurements. This thesis explored the association between physical activity and mental distress among the adolescents participating in the Tromsø Study: Fit Futures, using accelerometer measurements for physical activity and the two measuring points to study the association longitudinally. Regression analyses were conducted to investigate the potential relationship between change in objectively measured physical activity and change in mental distress, and associations between both objectively measured sedentary time and self-reported screen-time and mental distress. The relationship of mental distress to both physical activity and sedentary behaviour was more deeply explored when investigating potential mediating factors, peer acceptance, enjoyment of physical activity or perceived barriers towards physical activity. The overall results showed that, in the sample of adolescents participating in the Fit Futures study, there are no longitudinal associations between change in objectively measured physical activity and change in mental distress, nor is there a longitudinal association between objectively measured sedentary behaviour and mental distress. There was a significant longitudinal association between self-reported screen-time and mental distress for the adolescents, and there were results showing that low peer acceptance mediated the relationship between mental distress and both objectively measured physical activity and sedentary behaviour. These results suggest that the discrepancy in the literature is a consequence of the use of different methods of measurements and the complexity of the association between physical ...